Research discussion groups as a component of the development of practical skills of students in the field of training “Construction” - N. I. Taraseeva; O. V. Baulina; N. A. Dezhinova (Открытое образование (Москва), 2019)
The modern educational process, including theoretical and practical development of the basic educational program, provides that 40% of the basic information the student is receiving during the classes, the remaining 60% — for self-study. Research, practical and creative discussion groups in educational institutions of different levels (school, college, University) are helping talented and interested young people to develop their abilities and find their practical application. At the same time, significant assistance is provided by the use of modern teaching methods through long distance education, including systems of electronic educational and methodical complexes of disciplines and practices; systems that provide interactive communication of all subjects of the educational process, including industrial enterprises.The purpose of this article is to analyze the efficiency of research discussion groups in educational institutions of the construction areas with the aim of generating interest in the chosen occupation, the development of creative skills of the talented youth, opportunities to exercise their author’s ideas and inventive work “products" on the market of goods and services, as well as the development implementation into the educational process of schools and attract pupils to project work in view of the networking cooperation on the regional cyber platform. The role of the head of the group is to arouse the interest of students to the proposed research topics, to teach them to use computer technology not only to search for data on new technical solutions, but also to exchange information between the participants of the educational process, i.e. search for like-minded people, including from other educational institutions in different regions.Work in research groups of technical creativity in many respects facilitates process of development of occupations and specialties, gives the chance to expand and deepen area of knowledge, allows students to direct process, and for teachers to transfer part of this experience to occupations in classes to large audience, to involve all wishing to new projects.This makes it possible to obtain better knowledge, increase the level of training and high learning outcomes of students and pupils, preparing them for admission to universities by increasing motivation through a variety offorms of technology, including e-learning, on-line training. Modern working conditions make competitive those graduates who can prove their professional versatility, diversity of knowledge and interests, high adaptability to any working conditions, as well as a high potential for self-development. In the current labor market conditions, there is a demand exclusively for highly qualified specialists of vocational professions, mid-level specialists (group leader, craftsman) and senior personnel (for example, site supervisor). In such circumstances, one diploma of education is not enough for those who want to move quickly up the career ladder.Thus, at low costs for the transfer and exchange of information (knowledge and experience), we are able to provide both individual and collective way of development of research and creative abilities of students, to form persons, interested in further self-development, and as a result — the graduates, prepared for professional activity.